"Black" Titania Coatings Composed of Sol–Gel Imprinted Mie Resonators Arrays. (23rd November 2016) - Bottein, Thomas; Wood, Thomas; David, Thomas; Claude, Jean Benoît; Favre, Luc; Berbézier, Isabelle; Ronda, Antoine; Abbarchi, Marco; Grosso, David
Abstract : Optical technologies and devices rely on the controlled manipulation of light propagation through a medium. This is generally governed by the inherent effective refractive index of the material as well as by its structure and dimensionality. Although a precise control over light propagation with sub‐wavelength size objects is a crucial issue for a plethora of applications, the widely used fabrication methods remain cumbersome and expensive. Here, a sol–gel dip‐coating method combined with nanoimprinting lithography on arbitrary glass and silicon substrates is implemented for the fabrication of TiO2 ‐based dielectric Mie resonators. The technique allows obtaining sub‐micrometric pillars featuring unprecedented vertical aspect ratios (>1) with relatively high fidelity and precision. Spectroscopic characterization at visible and near‐infrared frequencies demonstrate that the resonant properties of these dielectric pillar arrays allow for a drastic reduction of light transmission (cutting more than 50% on glass) and reduced reflection (reflecting less than 3% on glass and 16% on bulk silicon), accounting for an efficient light trapping. These results provide a guideline for the fabrication of Mie resonators using a fast, versatile, low‐cost, low‐temperature technique for efficient light manipulation at the nanoscale. Abstract : Titania‐based dielectric Mie resonators (MRs) are fabricated via a joint sol–gel dip‐coating and soft‐nanoimprint lithography method . The coating of SiO2 glass substrates with TiO2 MRs allows for large modifications of light propagation, leading to reduced reflection and transmission owing to an efficient light trapping effect. The same fabrication methodology applied to a silicon substrate produces an efficient broad band antireflection coating.